ANALISIS SISTEM PENGENDALIAN INTERNAL ATAS PERSEDIAAN SPARE PARTS PADA PT. UNITED TRACTORS TBK CABANG SAMARINDA - ., Fitriany (EKONOMIA, 2013)
The research objective of this thesis is to determine the extent to whether the company PT. United Tractors Tbk is there a good Control Internal control and know the systems and procedures in the company inventory records.            Inventory is one element of current assets in the balance sheet, it is necessary for security is good and wise for the company to obtain optimal results in their activities. Internal control over inventory should be done in order to avoid the presence of a fault that occurred due to human error (human error) in terms of inventory miscalculation, it is necessary to the holding of a physical examination (stock taking) on a regular basis and avoid the damage and loss of supplies.            Authors conducted an analysis of the system of internal control over inventory of spare parts at PT. United Tractors Tbk with Comparative Method (comparison), which compares the internal control system established by the Company's internal control system according to the literature and use the flow chart (flow charts). Attached also shaped Questionnaire interview process, which means that according to the data by using a question and answer with the relevant parts.            Mention the results of the analysis of accounting systems and procedures pesediaan at PT. United Tractors Tbk has met a good internal control is supported by the results of a 30 item questionnaire answered question 27 items, 27/30 x 100% = 90% This means that PT. United Tractors Tbk has met the elements of a good internal control system.             Based on the above it can be seen that the authors hypothesis is rejected, because the system of internal control by the company's inventory dterapkan've done well.